Intratumoral pseudoaneurysms in hepatocellular carcinoma: do they occur de novo without any prior intervention? A tertiary care center experience of 6 years. (September 2015) - Haider, Zishan; Idris, Muhammad; Sajjad, Zafar; Humayun, Sidra; Kashif, Nazia; Ali, Sajjad
Background: Intratumoural pseudoaneurysms (ITPA) within hepatocellular carcinomas (HCC) usually arise as postprocedural complications of endovascular therapies or surgical procedures. Their de novo presence in HCC without any prior interventions has not been adequately described in medical literature. Purpose: To evaluate and quantify the presence of intratumoural pseudoaneurysms (ITPA) within hepatocellular carcinomas (HCC) prior to any intervention. Material and Methods: Retrospective cross-sectional review of 519 patients with HCC at a tertiary care university hospital with the purpose to evaluate and quantify the presence of ITPA present prior to any therapy. Patients' baseline data along with viral marker status, alpha fetoprotein (AFP) levels, imaging findings, and any prior treatment provided were recorded. Multi-detector computed tomography (MDCT) scans of selected patients were reviewed for presence of any ITPA and their incidence was calculated. Results: ITPAs without any prior therapy were found in 5% (25/519) of patients with HCC. Seventeen of 25 (68%) patients had liver cirrhosis while eight of 25 (32%) patients were non-cirrhotic on imaging. Multiple ITPAs were seen in 44% (11/25) of patients. Eight percent (2/25) of patients had pseudoaneurysm-associated hemorrhage, 20% (5/25) had lung metastasis, 12% (3/25) had portal vein thrombosis, 8% (2/25) had hepatic vein thrombosis, and 16% (4/25) had peritumoral hematoma. The incidence of de novo ITPAs occurring in patients with HCC without any prior therapy or intervention was 0.24%. Conclusion: These cases provide a unique insight into an additional feature of HCC and usefulness of recognizing the ITPAs on imaging studies. Although de novo ITPAs in HCC are uncommon, occurring with an incidence rate of 0.24%, their presence in hypervascular hepatic lesion may point towards the diagnosis of HCC. Additionally, they should be accounted for in management planning as they can lead to complications of rupture and hemorrhage.